Preparation, surface and porous characterization of ecofriendly activated carbon produced from apricot stones - Pap Szabolcs (Proceedings of the International Symposium on Analytical and Environmental Problems, 2016)
This work presents a thermochemical approach toward controlled preparation of powdered activated carbons from lignocellulosic raw materials (apricot stones), as industrial byproducts and components of organic solid waste. The physicochemical changes of the biomass during thermochemical activation with H3PO4 obtained after carbonization at 500 C for 2 h have been investigated by means of Fourier Transform Infrared (FTIR) spectra, scanning electron microscopy (SEM) and Brunauer–Emmett–Teller (BET) technique. The BET surface area and total pore volume were as high as 1098.78 m2 /g and 0.5 cm3 /g, respectively. The experimental results indicated that the use of apricot stones as a precursor material for the preparation of activated carbon (AC) was feasible.